2020
DOI: 10.1037/xhp0000740
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent working memory load may increase or reduce cognitive interference depending on the attentional set.

Abstract: Perceptual grouping leads to interference when target and distractors are integrated within the same percept. Cognitive control allows breaking this automatic tendency by focusing selectively on target information. Thus, interference can be modulated either by goal-directed mechanisms or by physical features of stimuli that help to segregate the target from distractors. In three experiments, participants had to respond to the left-right direction of a central arrow, flanked by two arrows on each side. Sometime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…By contrast, the ANTI-Vea incorporates a second goal into the mindset, which is simultaneous to the first one-namely, to respond to the vertical displacement of the target. This type of increase in the working memory load has been found to reduce the flanker interference, leading to a lower congruency effect (Luna, Telga, et al, 2020). Indeed, the congruency effect we obtained for RT and percentage errors were less than half of the usually reported in the ANT in nonclinical adults (MacLeod et al, 2010).…”
Section: Attentional Networkmentioning
confidence: 45%
“…By contrast, the ANTI-Vea incorporates a second goal into the mindset, which is simultaneous to the first one-namely, to respond to the vertical displacement of the target. This type of increase in the working memory load has been found to reduce the flanker interference, leading to a lower congruency effect (Luna, Telga, et al, 2020). Indeed, the congruency effect we obtained for RT and percentage errors were less than half of the usually reported in the ANT in nonclinical adults (MacLeod et al, 2010).…”
Section: Attentional Networkmentioning
confidence: 45%
“…3). Indeed, the ~40 ms effect of executive control observed with the ANTI-Vea (for a specific analysis of this issue, see Luna, Telga, Vadillo, & Lupiáñez, 2020) is similar to those of phasic alertness and orienting, in contrast with other versions of the task which produce a much larger effect of executive control (between ~60 and ~100 ms; Callejas et al, 2004;Fan, McCandliss, Sommer, Raz, & Posner, 2002;Roca, Castro, López-Ramón, & Lupiáñez, 2011).…”
Section: Discussionmentioning
confidence: 84%
“…Note that the size of the interference observed with the ANTI-Vea (i.e., 44 ms in the RT for both task versions, and 0.51% and 0.61% in the errors for the standard and the online versions, respectively) seems to be smaller than that usually reported with the ANT (Fan et al, 2002), ANTI (Callejas et al, 2004), and ANTI-V (Roca et al, 2011) tasks. To account for this reduced interference, we recently conducted a separate study to specifically address this issue (Luna, Telga, Vadillo, & Lupiáñez, 2020d). In short, and after analyzing data collected from five different experiments, we concluded that, in comparison with the interference effect observed when only performing a flanker task (i.e., ~55 ms and ~3.5% of errors), the concurrent working memory load of performing the flanker and the EV task at the same time (1) reduces interference (i.e., ~33 ms and ~-0.5% of errors) when the EV task helps to perceptually segregate the target from distractors (i.e., detecting an infrequent vertical displacement of the target, as in the ANTI-Vea), but (2) increases interference (i.e., ~87 ms and ~10.0% errors) when the EV task boosts the perceptual grouping of the target and distractors (i.e., by detecting an infrequent horizontal displacement of the target, as in the previous ANTI-V; Roca et al, 2011) (Luna, Telga, et al, 2020d).…”
Section: Measuring the Classic Attentional Components In The Lab And Onlinementioning
confidence: 99%
“…To account for this reduced interference, we recently conducted a separate study to specifically address this issue (Luna, Telga, Vadillo, & Lupiáñez, 2020d). In short, and after analyzing data collected from five different experiments, we concluded that, in comparison with the interference effect observed when only performing a flanker task (i.e., ~55 ms and ~3.5% of errors), the concurrent working memory load of performing the flanker and the EV task at the same time (1) reduces interference (i.e., ~33 ms and ~-0.5% of errors) when the EV task helps to perceptually segregate the target from distractors (i.e., detecting an infrequent vertical displacement of the target, as in the ANTI-Vea), but (2) increases interference (i.e., ~87 ms and ~10.0% errors) when the EV task boosts the perceptual grouping of the target and distractors (i.e., by detecting an infrequent horizontal displacement of the target, as in the previous ANTI-V; Roca et al, 2011) (Luna, Telga, et al, 2020d). In any case, a nice property of the scores of the classic attentional functions with the ANTI-Vea task is that the three are of a similar size (~45 ms), in contrast to previous versions of the task, which provide a much larger measure for executive control.…”
Section: Measuring the Classic Attentional Components In The Lab And Onlinementioning
confidence: 99%